Review of Paraskevi Golia's Υμνώντας το έθνος. Ο ρόλος των σχολικών γιορτών στην εθνική και πολιτική διαπαιδαγώγηση, 1924-2010 [Praising the nation: The role of national day school commemorations in national and political-education policy, 1924-2010] - Papandreou, Zeta G. (Historein, 2014)
Paraskevi Golia, Υμνώντας το έθνος. Ο ρόλος των σχολικών γιορτών στην εθνική και πολιτική διαπαιδαγώγηση 1924-2010 [Praising the nation: The role of national day school commemorations in national and political-education policy, 1924-2010], Thessaloniki: Epikentro, 2011, 445 pp